PENGARUH TEKNIK BERBALAS PANTUN UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 5 PEKANBARU - Gunawati, Aulawi; Saam, Zulfan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the differences in the level of self-confidence before and after given the pantun reciprocated technique through group guidance and to know the effect of the pantun reciprocated technique to increase students' self-confidence. The study was conducted at SMA Negeri 5 Pekanbaru against 7 samples with purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The instrument used in this study was a questionnaire consisting of indicators of self-confidence. this study shows that there is a difference in self-confidence before and after given the pantun reciprocated technique through group guidance with a significance value of 0.018 <0.05. The confidence of 7 students who were previously in the low category experienced an increase after being given the pantun reciprocated technique through group guidance, some of which were in the high category. In addition, based on the Spearman rank test, it is known that there is a significant effect of the pantun reciprocated technique on students' self-confidence of 56.25% while 43.75% is influenced by other factors originating from within the student and from the student environment.Key Word: Pantun Reciprocated Technique, Self Confidence, Group Guidance